An Alarming Increase of Fungal Infections in Intensive Care Unit: Challenges in the Diagnosis and Treatment - Richa Gupta, Abida Malik, Meher Rizvi, Moied Ahmed (Journal of Applied Pharmaceutical Science, 2016)
Introduction: Fungal infections have risen exponentially and are a cause of significant morbidity and mortality in Intensive Care Unit. The study was done to assess the prevalence of fungal pathogens in ICU patients, their antifungal susceptibility profile and biofilm production.It also aimed at evaluating risk factors and outcome in patients infected with fungal pathogens. Material and Methods: Samples were collected aseptically from 210 ICU patients from February 2012 to November 2014.They were cultured and identified by standard microbiological techniques. Antifungal susceptibility was performed according to CLSI guidelines. Results: From 210 ICU patients, 52(24.7%) were fungal pathogens. Majority of the fungal pathogens were Candida species 42(82.3%) followed by Aspergillus fumigatus 10(19.2%). Prevalence of Candida species was highest among urinary tract infections 20(39.2%) while that of Aspergillus fumigatus among lower respiratory tract infections 9(17.6%).34.3% of C.albicans and 25% C. dubliniensis were resistant to fluconazole.40% of Aspergillus fumigatus were resistant to fluconazole and ketoconazole. 21.8% of C.albicans were resistant to nystatin. C. albicans 19(59.3%) followed by A. fumigatus 6(60%) were the most common biofilm producing fungal isolates. High degree of antibiotic resistance was exhibited by the biofilm film positive isolates compared with biofilm negative isolates. Patients with fungal infection had higher mortality rate (44.3%) as compared to 40% in patients with bacterial infection. Conclusion: Fungal infections are associated with a high mortality rate.This study confirms the importance of the epidemiological surveillance on fungal infections in the ICU setting for documenting species distribution and antifungal susceptibility patterns to guide therapeutic choices.
Keywords: Salicylic acid,antioxidant,cyclic voltammetry,redox potential.